The adption of ICT project management software to facilitate the transition to becoming a medium sized contractor - Savvides, Michael George (My University, 2015)
The research investigated the practices of some grade 4 contractors registered with the CIDB operating in Johannesburg, with the intention to establish the path they took in order to become a medium-size contractor. The research was based on the assumption that, in order for a small contractor to upgrade to a medium sized contractor and take on more complex projects, they need to upgrade their project management software first, before upgrading their CIDB rating. The research is premised on the supposition that the development of small and medium contractors contribute significantly to the country’s employment rate and economy. It was found that the majority of the respondents upgraded their project management software first before upgrading their CIDB rating, establishing the initial assumption to be true. Other success factors included being able to maintain and develop current staff, sustain adequate cash reserves, maintain good relationships with project stakeholders, ensure good company control, completing projects on time and within budget, and improving the company’s project management capabilities. The recommendations suggest that, as a result of South Africa’s weak economic state, it is advisable for grade 3 contractors to grow their respective companies at a consistent rate. Utilizing the project management software effectively, and to its full capabilities, is crucial. Training the staff that will be using the software is just as important. Keywords: Project Management Software; Small and Medium Contractors; Construction Industry Development Board.